STUDI KOMPARASI HUKUM POSITIF DAN HUKUM ISLAM TENTANG HAM - M. Akbar (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
The 1945 Constitution stipulates that everyone is entitled to personal,family, honor, dignity and property protection under his control, and is entitled toa sense of security and protection from the threat of fear of doing or not acting inrights. Likewise, the right to decent work and livelihood, freedom of associationand assembly, the right to express opinions either by word of mouth or in writing.In the view of Islamic law a human right is a right inherent in a person since in thewomb of his mother until he died, merupkan grace given by Allah SWT. whichmust be respected and respected by every human being. In the Qur'an it ismentioned that Allah (SWT) has given the right to live to all human beings, thenin the social life is not allowed arbitrarily against others. Islam gives the right ofpeople to express opinions, but Islam gives boundaries in order to respect therights of others, where in expressing opinions there should be no intention andwords for humiliation to a person or a certain group, for the sake of mutual peace.Therefore, the way in which the implementation of human rights is done throughthe division and limitation of duties, and established forms of guarantee on therights of citizens.